2010
DOI: 10.1055/s-0030-1265902
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Sleep: Physiology and Pathophysiology

Abstract: Aging effects on sleep are important to consider for the practicing pulmonologist due to the increase in prevalence of major respiratory disorders as well as the normal changes that occur in sleep patterns with aging. Typically, aging is associated with decreases in the amount of slow wave sleep and increases in stage 1 and 2 non–rapid eye movement sleep, often attributed to an increased number of spontaneous arousals that occur in the elderly. Elderly individuals tend to go to sleep earlier in the evening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 152 publications
(136 reference statements)
2
96
0
8
Order By: Relevance
“…These modifications could lead to a disability in blood gas homeostasis ( Janssens et al, 1999) but a greater ventilation allows arterial O 2 saturation to be maintained at a same or a higher level in hypoxia than in young people. The increase in HVR with aging could be linked to a greater occurrence of obstructive sleep apneas in elderly people (Edwards et al, 2010). Chronic intermittent hypoxia, associated with sleep apneas, is known to increase hypoxic chemosensitivity (Foster et al, 2005), probably through an increased production of reactive oxygen species (Pialoux et al, 2009).…”
Section: Marczakmentioning
confidence: 99%
“…These modifications could lead to a disability in blood gas homeostasis ( Janssens et al, 1999) but a greater ventilation allows arterial O 2 saturation to be maintained at a same or a higher level in hypoxia than in young people. The increase in HVR with aging could be linked to a greater occurrence of obstructive sleep apneas in elderly people (Edwards et al, 2010). Chronic intermittent hypoxia, associated with sleep apneas, is known to increase hypoxic chemosensitivity (Foster et al, 2005), probably through an increased production of reactive oxygen species (Pialoux et al, 2009).…”
Section: Marczakmentioning
confidence: 99%
“…Total daily sleep time is reduced and sleep becomes increasingly disrupted with aging (Ancoli-Israel, 2009; Bliwise, 1993; Edwards et al, 2010). Sleep disruption of healthy young and older adults is associated with increased production of inflammatory mediators (Frey et al, 2007; Haack et al, 2007; Irwin et al, 2006; Mullington et al, 2009; Simpson and Dinges, 2007; Vgontzas et al, 2003), including the cytokine tumor necrosis factor-α (TNF).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is widely known that the sleep phase can be somewhat advanced in elderly patients. 25,26 The TEQ prescribed to the subjects in our current study was found to negatively correlate with sleep onset time. Although we cannot precisely determine the causal relationship, higher doses of medication may be related to more advanced sleep onset time.…”
Section: Discussionmentioning
confidence: 54%